AGE-REALTED MACULAR DEGENERATION AND SERUM LEPTIN: A CASE–CONTROL STUDY - MAHERDA, LAKSHITA; JAIN, KALPANA; AGARWAL, PULAK; BHARGAWA, POONAM (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of this study was to evaluate the association of serum leptin levels with presence and severity of age-related macular degeneration (AMD). Methods: A hospital-based case–control study conducted on 84 patients (42 cases and 42 controls) of either sex complaining of diminution of vision aged 40 years and above between August 2019 and 2021. Results: Mean serum leptin level in cases was 1.55±0.99 ng/mL and control was 2.11±0.88 ng/mL (p<0.008). The serum leptin level was negatively correlated with early (1.06±0.99 ng/mL), intermediate (0.50±0.08 ng/mL), and dry age-related macular degeneration (ARMD) (0.29±0.12 ng/mL). However, we found higher serum leptin levels in exudative ARMD (2.58±0.99 ng/mL). Maximum number of cases were of exudative AMD (42.86%) followed by early AMD (33.34%) and intermediate and dry AMD (11.91% each). Conclusion: We found a decrease in serum leptin levels as disease severity increases from the early AMD to intermediate AMD and Dry AMD. However, the levels of serum leptin levels were higher in patients with exudative AMD. This may be due to some pathological process that is different in dry and exudative AMD. This can form the basis for further research in future.